Answer:
6(x - 1)(3x + 1)
Explanation:
Given
18x² - 12x - 6 ← factor out 6 from each term
= 6(3x² - 2x - 1) ← factor the quadratic
Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term
product = 3 × - 1 = - 3 and sum = - 2
The factors are - 3 and + 1
Use these factors to split the x- term
3x² - 3x + x - 1 ( factor the first/second and third/fourth terms )
= 3x(x - 1) + 1(x - 1) ← factor out (x - 1)
= (x - 1)(3x + 1)
Hence
18x² - 12x - 6 = 6(x - 1)(3x + 1) ← in factored form